Method for producing MAS glass bodies, powder mixture, MAS glass bodies, and use of MAS glass bodies
Patent Information
- Application Number
- JP2026520725
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-06
- Filing Date
- 2024-09-02
- Publication Date
- 2026-10-22
Smart Images

Figure 2026535051000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a method for producing an MAS glass body, a powder mixture for producing an MAS glass body, an MAS glass body, and the use of the MAS glass body according to the present invention. BACKGROUND ART
[0002] Plasma-assisted dry etching (also referred to as "plasma etching" for short) is an indispensable technology in the production of ultra-fine structures of semiconductor elements, the production of high-resolution displays, and the production of solar cells.
[0003] European Patent Application Publication No. 3708547 (EP 3 708 547 A1) describes plasma etching in a vacuum reactor under a relatively high-temperature and highly corrosive atmosphere. Here, the vacuum reactor is purged with a low-pressure etching gas. Highly reactive etching-active plasma is generated by high-frequency discharge or electrodeless microwave discharge between electrodes.
[0004] In plasma etching, not only the desired layer is removed from the wafer to be processed, but also, as an undesirable side effect, components of the etching chamber, which are typically made of fused silica glass, are removed.
[0005] Fused silica glass is particularly suitable because it is relatively etching-resistant to the fluorine-containing plasma used. Furthermore, fused silica glass can be produced with very high purity. This is particularly important for use in components for plasma etching chambers, because possible impurities in the fused silica glass may reach the wafer during the etching process. The purer the etched fused silica glass, the lower the risk of contamination of the wafer during the plasma etching process. Therefore, for demanding etching steps, inter alia, fused silica glass components made of synthetic material with a purity of almost 100% are used.
[0006] The fewer impurities a plasma etching chamber component contains, the more suitable the material is, in principle, for this demanding application. This general understanding also applies to high-quality ceramics, which are partially used as a substitute for quartz glass in plasma etching chambers due to their high etching resistance.
[0007] From the perspective of applications in etching processes, it is known that all foreign matter should be avoided because it can contaminate the wafer in the plasma process. Therefore, prior art has shown that the highest possible purity of the manufactured glass components and, consequently, the starting materials used should always be obtained, which corresponds to minimizing all foreign matter.
[0008] A low etching rate of the materials or components used can also be advantageous, because the less material removed, the lower the risk of contamination. Furthermore, a low etching rate of components in the etching chamber is advantageous from the standpoint of very precise geometric shapes, which is especially important when the width of the structure is less than 10 nm. A lower etching rate results in less change in the geometric shape of the component during its lifecycle.
[0009] For example, U.S. Patent No. 7,015,163 B2 or U.S. Patent No. 7,084,084 B2 indicates that MAS glass is highly resistant to plasma etching processes in a fluorine-containing gas atmosphere. During the etching process, fluorine in the etching atmosphere reacts with magnesium in the MAS glass to form a non-volatile MgF2 layer on the surface of the component, which significantly reduces further etching removal.
[0010] International Publication No. 2022 / 075687 (WO 2022 / 075687 A1) further discloses that additional MgF2 doping is performed on MAS glass. However, it has been shown that such doping only slightly improves etching resistance.
[0011] MgO-Al2O3-SiO2 glass (MAS glass) exhibits very different physical and chemical properties depending on its chemical composition. As shown in Figure 1, various compositions are described in the literature under different names.
[0012] When using MAS glass for etching applications, it is crucial that the glass is completely X-ray amorphous, because crystalline regions introduce localized variability in etching removal. These effects, also known as etching non-uniformity, easily lead to "under-etching" and, consequently, particle generation.
[0013] Despite the known advantages of MAS glass, no industrially attractive products using it have been identified. MAS glass is known in the form of fibers, which are preferred for enhancing mechanical strength. Attempts have also been made to produce lightweight (weighing <1 kg) thin-walled ring components. However, for industrially attractive use, dense, heavy semi-finished products are required, such as cylinders or rods that can be cut into rings or plates of desired target dimensions.
[0014] From the geometric shape of any object, it is known that as volume increases, the ratio of surface area to volume (S / V) decreases because surface area increases with the square of its size, while volume increases with the cube of its size (the square-cube law). This is critically important for the cooling rate of objects of different sizes. The cooling rate is proportional to the size of the surface area, but since surface area increases more slowly than volume as the object gets larger, larger objects cool more slowly than smaller objects.
[0015] MAS glass must be rapidly cooled from its melting point of approximately 1300°C to 1000°C because, based on its chemical properties, it has a strong tendency towards crystallization and phase separation. Both of these effects have a very negative impact on the further processing and use of the material in plasma etching processes.
[0016] Therefore, it seems impossible to manufacture large, heavy, and dense MAS components while avoiding crystallization and phase separation due to the gradually slowing cooling rate.
[0017] To investigate the properties of MAS glass in more detail, we manufactured glasses with various chemical compositions and examined their effects on phase separation and crystallization tendencies. The chemical glass compositions of these 13 MAS samples are summarized in Table 1 and shown in the phase diagram in Figure 2.
[0018] [Table 1] Table 1: Glass composition [mol%] of manufactured MAS glass samples
[0019] Each laboratory sample weighed 300g.
[0020] The glass quality was evaluated using samples 0-12 shown in Figure 2, and the glass was evaluated as follows: Gray (Samples 2, 4, 7, 8, 9, 10): Transparent glass Hatching (Samples 3, 5, 6, 11, 12): Glass with air bubbles White (Samples 0, 1): Glass exhibiting phase separation.
[0021] It is shown that there is a preferred range of MAS composition that yields an attractive glass without an increase in bubble content and without spontaneous phase separation. This range is in the following region: • SiO2: 50~65 mol% • MgO: 25-35 mol% Al2O3: 10-25 mol%.
[0022] If the SiO2 content is too high (>70%), the glass cannot be sufficiently refined, and thus contains a large number of bubbles.
[0023] If the Al2O3 content is too low (<10%), MgO will not dissolve well in the glass, and spontaneous phase separation will occur.
[0024] With respect to etching resistance, it has been found that Glass Composition 2, namely 60 mol% SiO2, 30 mol% MgO, and 10 mol% Al2O3, is advantageous. However, since this glass is close to the range of spontaneous phase separation, it is particularly difficult to produce heavy and dense parts.
[0025] The position of the critical temperature range for phase separation was investigated by subjecting samples of Glass Composition 2 to temperature treatment. For this purpose, the samples were placed in a furnace having a pre-regulated temperature and held there for 60 minutes. These samples are shown in Figure 3.
[0026] Upon observing the samples according to Figure 3, it is clear that the temperature range from 1300°C to 1000°C is critical for the formation of phase separation. Therefore, it is particularly important to rapidly pass through this temperature range when technically producing parts from MAS glass.
[0027] The fact that large and dense parts are particularly susceptible to phase separation has been experimentally confirmed in the production of ring-shaped parts as follows: In order to achieve particularly high-purity glass that is inherently desirable for use in etching processes in semiconductor manufacturing, synthetic-purity starting materials were used: · SiO2: synthetic, impurities <1 ppm · Al2O3: synthetic, impurities <10 ppm · MgO: synthetic, impurities <30 ppm.
[0028] By weighting the impurities according to the mass proportions of the individual components of the glass composition, the total impurity content of the glass, that is, the proportion of all chemical elements other than Si, Al, Mg, or O, is less than 10 ppm.
[0029] The inner diameter of the ring-shaped component was 300 mm, the outer diameter of the ring-shaped component was 400 mm, and the height of the ring-shaped component was 25 mm.
[0030] At these dimensions, the density of the glass is 2.6 g / cm³. 3 The weight of the part is 3.57 kg, and the surface area / volume ratio is 1.2 cm². -1 This is the result.
[0031] Surprisingly, the heavy and dense components produced according to this recipe were found to exhibit strong phase separation after cooling from the molten material. Figure 4 shows the produced component, i.e., a heavy and dense component made of MAS glass using synthetic purity raw materials, and the resulting phase separation. The phase separation shown in Figure 4 is particularly surprising because, with this glass composition, transparent glass can be produced in laboratory experiments using a 300g sample (see sample 2 in Figure 2).
[0032] The phase separation is not very pronounced, as shown in Figure 3, and exhibits a somewhat different appearance, but electron microscopy confirmed that the phenomenon is droplet-like phase separation.
[0033] These experiments very impressively demonstrate how critical the effects of phase separation are for the manufacturing of MAS components. Therefore, it is clear that phase separation must be avoided as much as possible during the manufacturing process of MAS components.
[0034] In this process, in addition to ensuring good homogenization of the MAS glass during the melting process, the time it takes for the sample to cool from over 1300°C to 1000°C is crucial. Significant phase separation can occur at this stage, so minimizing this time is essential.
[0035] When manufacturing heavy, dense objects, the increasing weight creates a physical limitation: the surface area / volume ratio becomes increasingly unfavorable (the square-cube law). Since volume increases with the cube but surface area only increases with the square, removing thermal energy from the central region of the MAS component becomes increasingly difficult. Consequently, the core of the material remains in the critical temperature region of 1000°C to 1300°C for longer.
[0036] Figure 5 clearly illustrates this effect of temperature distribution when cooling heavy, dense samples. It shows that the heavy, dense MAS material maintains a high temperature for an extended period in its core region during cooling. This exemplifies the high heat capacity and low heat removal required when manufacturing glass bodies with a mass > 3 kg.
[0037] However, based on these physical boundary conditions, the cooling time in the critical temperature range of over 1300°C to 1000°C can only be shortened to a limited extent. [Prior art documents] [Patent Documents]
[0038] [Patent Document 1] European Patent Application Publication No. 3708547 [Patent Document 2] U.S. Patent No. 7015163 [Patent Document 3] U.S. Patent No. 7084084 [Patent Document 4] International Publication No. 2022 / 075687 [Overview of the Initiative] [Problems that the invention aims to solve]
[0039] Therefore, the object of the present invention is to eliminate the drawbacks of the prior art described above. In particular, a dense and large MAS glass body that is homogeneous and has minimal crystallization and phase separation during hardening should be provided in an easy manner. Furthermore, the MAS glass body should be X-ray amorphous. Here, the MAS glass body should have a weight of more than 3 kg and a thickness of 1.5 cm. -1 The following surface area / volume ratios should be observed. [Means for solving the problem]
[0040] These problems were, surprisingly, solved by the method for producing the MAS glass body according to claim 1, by the powder mixture for producing the MAS glass body according to claim 8, by the MAS glass body according to claim 11, and by the use of the MAS glass body according to claim 15.
[0041] Further advantageous configurations are described in the dependent claims.
[0042] Numerous specific details are described below to enable a comprehensive understanding of the subject matter of this invention. However, it will be apparent to those skilled in the art that the subject matter can be implemented and modified without these specific details.
[0043] All features of one embodiment can be combined with features of other embodiments, provided that the features of various embodiments are compatible.
[0044] The terms used in this disclosure are used solely to describe specific embodiments and should not be understood as limitations of scope. The singular forms “one” and “it” as used herein and in the claims should be understood to include the plural unless the context clearly indicates otherwise. Conversely, the plural also includes the singular. Furthermore, the terms “and / or” as used herein should be understood to include all possible combinations of one or more of the enumerated elements in question. In addition, the terms “encompassing,” “inclusion,” “containing,” and / or “containing,” as used herein and in the claims, identify the presence of the described features, stages, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, stages, operations, elements, components, and / or groups thereof.
[0045] In this specification and in the claims, the terms “contains,” “includes,” and / or “includes” may also mean “consist of,” that is, the presence or addition of one or more other features, stages, operations, elements, components, and / or groups.
[0046] The present invention • Mass ≥ 3 kg, and • Surface area / volume ratio ≤ 1.5 cm² -1 A method for producing an X-ray amorphous MAS glass body, comprising the following steps: a) Prepare a powder mixture containing 10-40 mol% MgO, 5-30 mol% Al2O3, and 40-70 mol% SiO2, or precursors of these raw materials, as well as auxiliary elements and heterogeneous elements, where, The aforementioned auxiliary elements are elements of Group 1 (I. Hauptgruppe) and / or Group 2 (II. Hauptgruppe) and / or Group 14 (IV. Hauptgruppe) and / or Fe. The total content of the auxiliary elements and heterogeneous elements is adjusted to at least 10 ppm to 300 ppm, particularly at least 30 ppm to 150 ppm, and especially preferably at least 50 ppm to 100 ppm. b) A step of melting the powder mixture prepared in step a), c) A step in which the molten material produced in step b) is cooled, and the cooled molten material is pulverized into particles having a diameter of ≤10 mm. d) A step of heating and melting the particles obtained in step c), and e) A step in which the molten material obtained in step d) is cooled. The present invention relates to the present invention relating to the present invention having
[0047] As precursors to these raw materials, corresponding hydroxides and / or carbonates of MgO and Al2O3 are advantageously understood.
[0048] The proportions of individual elements shown in step a) are advantageously determined by LA-ICP-MS (laser ablation inductively coupled plasma mass spectrometry). This method is also advantageously applicable to all further listed descriptions of content or proportion in the powder mixture and / or MAS glass bodies.
[0049] Surprisingly, it has been confirmed that adding auxiliary elements to the powder mixture allows for the production of heavy and dense MAS glass bodies with significantly improved crystallization and phase separation.
[0050] Advantageously, the addition of auxiliary elements increases the entropy of the molten material, in particular. This increase in entropy significantly reduces the tendency for phase separation in the molten material.
[0051] Here, it is based on entropy of mixing:
number
[0052] The addition of auxiliary elements leads to a significant increase in entropy, which in turn governs Gibbs' free enthalpy:
number
[0053] Entropy is positive, and therefore its contribution to free enthalpy is negative, which means that when entropy is high, the mixed state is energetically favorable. Therefore, according to this invention, when auxiliary elements are present, the molten material remains mixed instead of undergoing phase separation.
[0054] According to this invention, the auxiliary elements are alkalis and / or alkaline earth metals and / or Fe. These auxiliary elements enable the production of particularly good, dense, and large MAS glass bodies with little to no phase separation. At the same time, the MAS glass bodies thus produced are suitable for use in semiconductor manufacturing processes, as demonstrated by tests.
[0055] As auxiliary elements, in particular, the proportion of these elements in the prepared powder mixture is such that it prevents phase separation during the production of the MAS glass body.
[0056] Advantageously, auxiliary elements are added during the preparation of the powder mixture, specifically during the preparation of the MgO-Al2O3-SiO2 mixture.
[0057] With respect to alkali and / or alkaline earth metals, Na and / or K and / or Ca and / or Li are particularly preferred as auxiliary elements.
[0058] Advantageously, a mixture of at least two elements of Na, K, Ca, Li, and Fe is used.
[0059] Therefore, within the scope of the method according to the present invention, a MgO-Al2O3-SiO2 mixture having auxiliary elements is explicitly prepared. Thus, according to the present invention, there is a departure from the standard procedure of using a powder mixture that is as pure as possible without additional elements.
[0060] Particularly preferable, the powder mixture is prepared by adjusting the content of auxiliary elements as follows: • Sodium content: at least 2 ppm to 50 ppm, and / or • K content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Ca content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Li content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Fe content: at least 0.5 ppm to 10 ppm, especially at least 1 ppm to 5 ppm.
[0061] The heterogeneous elements contained in the prepared powder mixture are preferably elements of Group 13 (III. Hauptgruppe) and / or Group 15 (V. Hauptgruppe), and / or transition metals other than Fe.
[0062] Here, the concentrations of heterogeneous elements are favorably adjusted such that the concentrations of Cr, Mn, Co, Ni, Ti, Zn, and Zr are each <2 ppm, and / or the concentrations of B, P, and Cu are each <1 ppm.
[0063] Advantageously, in step a), a powder mixture is prepared containing 25-35 mol% MgO, 10-25 mol% Al2O3, and 50-65 mol% SiO2, particularly preferably 30 mol% MgO, 10 mol% Al2O3, and 60 mol% SiO2.
[0064] In a preferred embodiment, the method according to the present invention is characterized by adding less than 0.01 mol% of a material additive containing fluorine and / or a yttrium compound during the preparation of the powder mixture and / or the production of the MAS glass body.
[0065] Advantageously, steps b) and / or c) are carried out by exposure to temperatures of 1200°C to 2000°C, preferably 1500°C to 1750°C.
[0066] In a preferred embodiment, the method according to the present invention is characterized in that steps c), d), and e) are performed multiple times, and the molten material in step c) is each a molten material previously produced in step e). Multiple times means a number of times such as 2, 3, 4, 5, etc. By performing steps c), d), and e) multiple times, homogeneity can be further improved.
[0067] In a preferred embodiment, the method according to the present invention is characterized in that the time of step b) is 0.1 to 10 hours, preferably 0.1 to 7 hours.
[0068] In a preferred embodiment, the method according to the present invention is characterized in that the time of step d) is 0.1 to 10 hours, preferably 0.1 to 7 hours.
[0069] In a preferred embodiment, the method according to the present invention is characterized by cooling the mixture from step d) to a temperature of less than 25°C in step e).
[0070] In a more preferred embodiment, the method according to the present invention is characterized in that, in step d), the molten material from step d) is first rapidly cooled to a temperature of 600 to 900°C, and then subsequently cooled at a remarkably low rate to a temperature of less than 25°C.
[0071] Rapid cooling means, for example, cooling above 75K / min, preferably above 90K / min, and below 120K / min. Slow cooling means, for example, cooling below 5K / min, preferably below 2.5K / min, and above 0.5K / min.
[0072] Rapid cooling to a temperature range of 600-900°C has the advantage of minimizing the risk of crystallization, thereby further avoiding the formation of heterogeneity. Subsequent slow cooling to room temperature avoids the formation of stress or cracks.
[0073] In a preferred embodiment, the method according to the present invention is characterized in that the heating of the mixture in step b) and / or d) is carried out in a Pt and / or Pt / Rh crucible.
[0074] In a preferred embodiment, the method according to the present invention is characterized in that the cooling of the molten material in step e) is first carried out in a steel mold coated with a release agent, and subsequently in a cooling furnace after demolding.
[0075] Further, and especially parallel, aspects of the present invention relate to powder mixtures for producing X-ray amorphous MAS glass bodies, and more particularly to powder mixtures for use in the method according to the present invention.
[0076] The powder mixture contains 10-40 mol% MgO, 5-30 mol% Al2O3 and 40-70 mol% SiO2, or precursors of these raw materials, preferably 25-35 mol% MgO, 10-25 mol% Al2O3 and 50-65 mol% SiO2, or precursors of these raw materials, particularly preferably 30 mol% MgO, 10 mol% Al2O3 and 60 mol% SiO2, or precursors of these raw materials. The powder mixture further contains auxiliary elements and heterogeneous elements, wherein the auxiliary elements are elements of Group 1 (I. Hauptgruppe) and / or Group 2 (II. Hauptgruppe) and / or Group 14 (IV. Hauptgruppe) and / or Fe. The total content of auxiliary elements and heterogeneous elements is 10 ppm to 300 ppm, particularly 30 ppm to 150 ppm, and especially preferably 50 ppm to 100 ppm.
[0077] The method according to the present invention brings about advantages similar to those already described.
[0078] Advantageously, the auxiliary elements are alkali and / or alkaline earth metals, particularly Na and / or K and / or Ca and / or Li and / or Fe, and advantageously a mixture of at least two of the elements Na, K, Ca, Li and Fe.
[0079] Particularly preferred, • Sodium content: at least 2 ppm to 50 ppm, and / or • K content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Ca content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Li content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Fe content: at least 0.5 ppm to 10 ppm, especially at least 1 ppm to 5 ppm That is the case.
[0080] The powder mixture advantageously contains less than 0.01 mol% of material additives, including fluorine and / or yttrium compounds.
[0081] The heterogeneous elements in the powder mixture according to the present invention are preferably elements of Group 13 (III. Hauptgruppe) and / or Group 15 (V. Hauptgruppe), and / or transition metals other than Fe.
[0082] Advantageously, the elemental content of Cr, Mn, Co, Ni, Ti, Zn, and Zr is <2 ppm each. Even more advantageously, the elemental content of B, P, and Cu is <1 ppm each.
[0083] Further, and especially parallel, aspects of the present invention relate particularly to MAS glass bodies that can be manufactured by carrying out the method according to the present invention.
[0084] The MAS glass body according to the present invention has a mass ≥ 3 kg and a surface area / volume ratio ≤ 1.5 cm². -1 It possesses the properties of an X-ray amorphous MAS glass body.
[0085] The MAS glass body contains 10-40 mol% MgO, 5-30 mol% Al2O3, and 40-70 mol% SiO2, preferably 25-35 mol% MgO, 10-25 mol% Al2O3, and 50-65 mol% SiO2, and particularly preferably 30 mol% MgO, 10 mol% Al2O3, and 60 mol% SiO2. The MAS glass body further contains auxiliary elements and heterogeneous elements. The aforementioned auxiliary elements are elements of Group 1 (I. Hauptgruppe) and / or Group 2 (II. Hauptgruppe) and / or Group 14 (IV. Hauptgruppe) and / or Fe. The total content of auxiliary elements and heterogeneous elements is 10 ppm to 300 ppm, particularly 30 ppm to 150 ppm, and especially preferably 50 ppm to 100 ppm.
[0086] The same or similar advantages as those already described in relation to the method according to the present invention are obtained.
[0087] X-ray amorphous MAS glass bodies are glass without broad regions of crystalline long-range order, and therefore produce only very broad X-ray reflections during appropriate inspections (so-called glass halos).
[0088] In the context of this invention, "X-ray amorphous" means that there are no crystalline regions larger than 10 nm in the MAS glass body, which can be identified, for example, by a diffraction apparatus.
[0089] Advantageously, the auxiliary elements are alkali and / or alkaline earth metals and / or Fe.
[0090] With respect to alkali and / or alkaline earth metals, the auxiliary elements are particularly preferably Na and / or K and / or Ca and / or Li.
[0091] Advantageously, the MAS glass body has a mixture of at least two elements: Na, K, Ca, Li, and Fe.
[0092] Particularly preferred, • Na content: at least 2 ppm to 50 ppm, and / or • K content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Ca content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Li content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Fe content: at least 0.5 ppm to 10 ppm, especially at least 1 ppm to 5 ppm That is the case.
[0093] The MAS glass body advantageously contains less than 0.01 mol% of material additives, including fluorine and / or yttrium compounds.
[0094] The heterogeneous elements of the MAS glass body according to the present invention are preferably elements of Group 13 (III. Hauptgruppe) and / or Group 15 (V. Hauptgruppe), and / or transition metals other than Fe.
[0095] Advantageously, the elemental content of Cr, Mn, Co, Ni, Ti, Zn, and Zr is <2 ppm each. Even more advantageously, the elemental content of B, P, and Cu is <1 ppm each.
[0096] Based on the described content of the heterogeneous elements, elements that may promote crystallization, such as Ti and Zr, are kept very low or, advantageously, avoided. Furthermore, the MAS glass body according to the present invention has a composition that is not harmful to semiconductor manufacturing processes.
[0097] MAS glass bodies can have a ring shape, a cylindrical shape, or a rod shape. Forming a cylindrical shape allows, for example, the subsequent manufacture of ring-shaped MAS glass components.
[0098] The present invention further relates to a component including the aforementioned MAS glass body.
[0099] Herein, all the definitions and preferred embodiments of the method and the MAS glass body according to the present invention also apply similarly to the components.
[0100] In preferred embodiments, the MAS glass body according to the present invention or components manufactured from the MAS glass body according to the present invention are used in semiconductor manufacturing, advantageously in etching chambers.
[0101] The use of the MAS glass body described in this invention also relates to the MAS glass body produced by the method according to the present invention.
[0102] Herein, all the definitions and preferred embodiments of the method and the MAS glass body according to the present invention also apply similarly to the use of the MAS glass body and / or components. [Brief explanation of the drawing]
[0103] [Figure 1] This figure shows the composition of MgO-Al2O3-SiO2 glass. [Figure 2] This figure shows the phase diagram of the chemical glass composition of the MAS sample. [Figure 3] This diagram shows the relationship between temperature and phase separation. [Figure 4] This is a diagram showing the resulting phase separation. [Figure 5] This figure shows the temperature distribution when cooling a heavy, dense MAS material. [Figure 6] This figure shows a ring-shaped MAS glass body. [Examples]
[0104] The present invention will be described in more detail below using examples that are not limited thereto.
[0105] Example 1: A powder mixture was prepared to produce MAS glass bodies, in which oxides of the elements Si, Al, and Mg were weighed and mixed as starting materials in the following composition: MgO: 30 mol% • Al2O3: 10 mol% • SiO2: 60 mol%.
[0106] The proportions of auxiliary elements and heterogeneous elements were adjusted to 60 ppm during mixing, where, · Ca content: 10ppm · Fe content: 1.5ppm · Na content: 35ppm · K content: 6ppm • Content of heterogeneous elements, i.e., Mn, Cr, and Zr: <1 ppm It was adjusted to that.
[0107] A 300g sample was melted in a Pt / Rh crucible at 1650°C for 3 hours. Subsequently, the molten material was poured into cold deionized water.
[0108] The resulting frit was crushed and melted again at 1650°C for 6 hours and 40 minutes. The molten material was observed to determine the second melting time, and it was melted until it was clear and bubble-free.
[0109] After the second melting process, the glass was poured into a metal mold.
[0110] A transparent MAS glass body without phase separation was obtained.
[0111] Example 2: In a further example, a powder mixture was prepared according to Example 1, and a 3 kg sample was produced. The pulverized frit was melted in a large Pt / Rh crucible and subsequently poured into a metal ring mold. A transparent ring with no phase separation was obtained, having an outer diameter of 400 mm, an inner diameter of 300 mm, and a height of 21 mm. This ring-shaped MAS glass body is shown in Figure 6 and shows no signs of phase separation.
Claims
1. • Mass ≥ 3 kg, and • Surface area / volume ratio ≤ 1.5 cm² -1 A method for producing an X-ray amorphous MAS glass body, comprising the following steps: a) 10-40 mol% MgO, 5-30 mol% Al 2 O 3 and 40-70 mol% SiO 2 or precursors of these raw materials, as well as powder mixtures having auxiliary elements and heterogeneous elements, wherein the auxiliary elements are elements of Group 1 and / or Group 2 and / or Group 14 and / or Fe. The total content of the auxiliary elements and heterogeneous elements is adjusted to at least 10 ppm to 300 ppm, particularly at least 30 ppm to 150 ppm, and especially preferably at least 50 ppm to 100 ppm. b) A step of melting the powder mixture prepared in step a), c) A step in which the molten material produced in step b) is cooled, and the cooled molten material is pulverized into particles having a diameter of ≤ 10 mm. d) A step of heating and melting the particles obtained in step c), and e) A step in which the molten material obtained in step d) is cooled. The method comprising the above.
2. The method according to claim 1, characterized in that alkali and / or alkaline earth metals, particularly Na and / or K and / or Ca and / or Li, and / or Fe, and preferably a mixture of at least two elements of Na, K, Ca, Li, and Fe, are used as auxiliary elements.
3. • Sodium content: at least 2 ppm to 50 ppm, and / or • K content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Ca content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or Li content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Fe content: at least 0.5 ppm to 10 ppm, especially at least 1 ppm to 5 ppm The method according to claim 2, characterized in that it is adjusted to the following.
4. The method according to any one of claims 1 to 3, characterized in that the heterogeneous element is an element of Group 13 and / or Group 15, and / or a transition metal other than Fe.
5. The method according to claim 4, characterized in that the content of the elements Cr, Mn, Co, Ni, Ti, Zn, and Zr is <2 ppm each, and / or the content of the elements B, P, and Cu is <1 ppm each.
6. In step a), 25 to 35 mol% of MgO, 10 to 25 mol% of Al 2 O 3 and 50 to 65 mol% of SiO 2 , particularly preferably 30 mol% of MgO, 10 mol% of Al 2 O 3 and 60 mol% of SiO 2 A method according to any one of claims 1 to 5, characterized in that a powder mixture comprising is prepared.
7. The method according to any one of claims 1 to 6, characterized in that step b) and / or c) are carried out by exposure to a temperature of 1200°C to 2000°C, preferably 1500°C to 1750°C.
8. A powder mixture for producing an X-ray amorphous MAS glass body, particularly a powder mixture for use in the method according to any one of claims 1 to 7, wherein the powder mixture comprises 10 to 40 mol% MgO and 5 to 30 mol% Al 2 O 3 and 40-70 mol% SiO 2 , or precursors of these raw materials, preferably 25-35 mol% MgO, 10-25 mol% Al 2 O 3 and 50-65 mol% SiO 2 , or precursors of these raw materials, particularly preferably 30 mol% MgO and 10 mol% Al 2 O 3 and 60 mol% SiO 2 , or having precursors of these raw materials, The aforementioned powder mixture further contains auxiliary elements and heterogeneous elements, The auxiliary element is an element of Group 1 and / or Group 2 and / or Group 14 and / or Fe, and The powder mixture wherein the total content of the auxiliary elements and heterogeneous elements is 10 ppm to 300 ppm, particularly 30 ppm to 150 ppm, and especially preferably 50 ppm to 100 ppm.
9. The auxiliary element is an alkali and / or alkaline earth metal, particularly Na and / or K and / or Ca and / or Li, and / or Fe, preferably a mixture of at least two elements of Na, K, Ca, Li and Fe. To have an advantage, • Sodium content: at least 2 ppm to 50 ppm, and / or • K content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Ca content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or Li content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Fe content: at least 0.5 ppm to 10 ppm, especially at least 1 ppm to 5 ppm The powder mixture according to claim 8, characterized in that it is the same as the one described above.
10. The aforementioned heterogeneous elements are elements of Group 13 and / or Group 15, and / or transition metals excluding Fe, which is advantageous. The powder mixture according to claim 8 or 9, characterized in that the content of each element Cr, Mn, Co, Ni, Ti, Zn, and Zr is <2 ppm, and / or the content of each element B, P, and Cu is <1 ppm.
11. MAS glass body, in particular an MAS glass body manufactured by the method described in any one of claims 1 to 7, Mass ≥ 3 kg, and surface area / volume ratio ≤ 1.5 cm² -1 The MAS glass body is X-ray amorphous, and 10-40 mol% MgO, 5-30 mol% Al 2 O 3 and 40-70 mol% SiO 2 , advantageously, 25-35 mol% MgO and 10-25 mol% Al 2 O 3 and 50-65 mol% SiO 2 Particularly preferably 30 mol% MgO and 10 mol% Al 2 O 3 and 60 mol% SiO 2 It has, The aforementioned MAS glass body further contains auxiliary elements and heterogeneous elements, The aforementioned auxiliary elements are elements of Group 1 and / or Group 2 and / or Group 14 and / or Fe. The MAS glass body wherein the total content of the auxiliary elements and heterogeneous elements is 10 ppm to 300 ppm, particularly 30 ppm to 150 ppm, and especially preferably 50 ppm to 100 ppm.
12. The auxiliary element is an alkali and / or alkaline earth metal, particularly Na and / or K and / or Ca and / or Li, and / or Fe, preferably a mixture of at least two elements of Na, K, Ca, Li and Fe. To have an advantage, • Sodium content: at least 2 ppm to 50 ppm, and / or • K content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Ca content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or Li content: at least 0.5 ppm to 50 ppm, especially at least 0.5 ppm to 20 ppm, and / or • Fe content: at least 0.5 ppm to 10 ppm, especially at least 1 ppm to 5 ppm The MAS glass body according to claim 11, characterized in that it is the same as the one described above.
13. The aforementioned heterogeneous elements are elements of Group 13 and / or Group 15, and / or transition metals excluding Fe, which is advantageous. The MAS glass body according to claim 11 or 12, characterized in that the content of the elements Cr, Mn, Co, Ni, Ti, Zn, and Zr is <2 ppm each, and / or the content of the elements B, P, and Cu is <1 ppm each.
14. The MAS glass body according to any one of claims 11 to 13, characterized in that the MAS glass body has a ring shape, a cylinder shape, or a rod shape.
15. Use in an etching chamber of the MAS glass body described in any one of claims 11 to 14, or a component manufactured from the MAS glass body described in any one of claims 11 to 14.
Citation Information
Patent Citations
Component consisting of doped quartz glass for use in a plasma enhanced production process, and method for producing said component
EP3708547A1
Glass member resistant to plasma corrosion
US7015163B2
Highly durable silica glass, process for producing same, member comprised thereof, and apparatus provided therewith
US7084084B2
Plasma-resistant glass and manufacturing method therefor
WO2022075687A1